Styles of Faith : Introduction to Theory and Research in Faith Development - Streib, Heinz, (Brill Research Perspectives in Humanities and Social Sciences., 2026)
From decades of conceptual and empirical work on faith development, the authors present the current state of theory and research. The understanding of faith is advanced from James Fowler's original Stages of Faith . With reference to Paul Tillich's notion of faith as ultimate concern and with reference to new developments in psychology and phenomenological philosophy, however, the authors sharpen what faith and faith style development could mean in today's jeopardized world and its rapidly changing religious landscapes. Theoretical considerations are supported by recent results about faith development based on data from two-decades-long empirical investigation in the USA and Germany.